Straw incorporation and nitrogen reduction effect on the uptake and use efficiency of nitrogen as well as soil CO2 emission of relay strip intercropped soybean - Zheng, Benchuan; Chen, Ping; Du, Qing; Yang, Huan; Luo, Kai; Wang, Xiaochun; Yang, Feng; Yong, Taiwen; Yang, Wenyu (Frontiers in Plant Science, 2022)
Intercropping can increase crop N uptake and reduce carbon emissions. However, the effects of straw incorporation and N reduction on N use and carbon emissions in intercropping are still unclear. We explored the mechanism of N uptake, N use efficiency, and CO2 emissions in the wheat-maize-soybean relay strip intercropping system. A two-year field experiment was conducted with two straw managements, i.e., wheat straw incorporation (SI) and straw removal (SR), and four N application levels of soybean, i.e., 60 (N60), 30 (N30), 15 (N15), and 0 kg N ha-1 (N0). We assessed soil properties, CO2 emissions, and characteristics of roots, nodules, and aboveground N uptake of intercropped soybean. Results showed that geometry mean diameter of aggregate, soil porosity, soil total N, and soil urease activity were notably greater in SI than in SR. N input reduced from N60 to N30 did not significantly affect the soil total N content and urease activity in SI. The root length, root surface area, root volume, root biomass, root bleeding intensity, and inorganic N content of bleeding sap were greater in SI than in SR. In the SI, although the root length and surface area peaked at N60, the root biomass and inorganic N content of bleeding sap were insignificant between N60 and N30. The nodule number, nodule dry weight, nodule nitrogenase activity, and nodule nitrogen fixation potential in SI were notably increased compared with SR. The nodule nitrogen fixation potential in SI notably increased with the decrease of N input at the R3 stage, but it peaked in N30 at the R5 stage. On average, the aboveground N uptake and nitrogen recovery efficiency (RE) was notably higher by 43.7% and 76.8% in SI than in SR. SI+N30 achieved the greatest aboveground N uptake and RE. The CO2 emission and accumulated CO2 emission were notably greater in SI than in SR, and the accumulated CO2 emission of SI was the lowest with N30 input. In conclusion, SI+N30 promoted N uptake and utilization efficiency with reduced CO2 emissions during the soybean cropping season. It provides a potential strategy for sustainable agricultural development in intercropping systems.